PEMANFAATAN VIRTUAL REALITY DALAM PENDIDIKAN PENERBANGAN: EVALUASI EFEKTIVITAS, TANTANGAN, DAN TRANSFER KETERAMPILAN MELALUI SYSTEMATIC LITERATURE REVIEW - Rahmat; Maksum, Hasan; Novaliendry, Dony (Jurnal Merah Putih Sekolah Dasar, 2026)
This research aims to evaluate the use of Virtual Reality (VR) technology in aviation education, with a focus on improving technical and non-technical skills, implementation challenges, and transferring skills to the real world. The method used is the Systematic Literature Review (SLR), which collects and analyzes scientific articles related to the use of VR in flight training. The results show that VR is effective in improving technical skills, such as aircraft navigation and aircraft control, as well as non-technical skills, such as decision-making and team communication in emergency situations. However, the main challenges facing aviation education institutions are cost and infrastructure, although VR provides significant benefits in terms of training flexibility and reduced reliance on physical simulators. Additionally, while VR improves skills in simulation, the transfer of those skills to the real world still requires further evaluation. In conclusion, VR has great potential to optimize flight training, but it requires integration with hands-on training in the field to ensure effective skill transfer. The study also suggests further research to develop more adaptive and effective VR training models in the context of aviation education.